2023
DOI: 10.3390/ma16124291
|View full text |Cite
|
Sign up to set email alerts
|

Reliability Evaluation of Board-Level Flip-Chip Package under Coupled Mechanical Compression and Thermal Cycling Test Conditions

Abstract: Flip Chip Ball Grid Array (FCBGA) packages, together with many other heterogeneous integration packages, are widely used in high I/O (Input/Output) density and high-performance computing applications. The thermal dissipation efficiency of such packages is often improved through the use of an external heat sink. However, the heat sink increases the solder joint inelastic strain energy density, and thus reduces the board-level thermal cycling test reliability. The present study constructs a three-dimensional (3D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The fourth is the Cu/Ni/Sn pillar, in which the Cu pillar is plated with a Ni layer, and then covered with tin balls. This not only retains the advantages of the high strength of In terms of external mechanical stress, Shih et al [69] found that when FCGBA assemblies are subjected to thermal cycling, the extra weight of the heat sink exerts additional mechanical stress on the solder joints, resulting in the solder balls at the corners of the uncovered FCBGA assemblies being more susceptible to more severe cracking. To eliminate the negative effects of external vibration and shock on package reliability, researchers have proposed several ways to improve the electrical interconnect structure.…”
Section: Damage By Thermal Stressmentioning
confidence: 99%
“…The fourth is the Cu/Ni/Sn pillar, in which the Cu pillar is plated with a Ni layer, and then covered with tin balls. This not only retains the advantages of the high strength of In terms of external mechanical stress, Shih et al [69] found that when FCGBA assemblies are subjected to thermal cycling, the extra weight of the heat sink exerts additional mechanical stress on the solder joints, resulting in the solder balls at the corners of the uncovered FCBGA assemblies being more susceptible to more severe cracking. To eliminate the negative effects of external vibration and shock on package reliability, researchers have proposed several ways to improve the electrical interconnect structure.…”
Section: Damage By Thermal Stressmentioning
confidence: 99%